Novel soil-pegged geogrid (PG) interactions in pull-out loading conditions. Issue 4 (August 2022) - Abdi, M.R.; Mirzaeifar, H.; Asgardun, Y.
Abstract: In current study, large-scale pull-out tests were conducted to examine the behavior of a novel reinforcement system named "Pegged Geogrid" (PG) under pull-out loading condition. Metal pegs were combined with geogrid to enhance resistance to pull-out. Incorporating pegs with geogrids alleviates bolting, welding, clamping, increasing geogrid length or making alterations to the geogrid as recommended by previous researchers. Peg roots are simply inserted/driven through apertures into the soil, nailing the geogrid to the lower and subsequently the upper backfill layers. Effects of soil particle size, normal pressure, peg length, width, and numbers has been evaluated using two sandy and a gravely soil. Results show that inclusion of pegs significantly enhances soil passive resistance contribution to pull-out. Increasing the width and number of pegs, resulted in enhancing passive soil resistance activation in front of the bearing surfaces and thus greater pull-out resistance augmented by soil particle size and normal pressure. Displacements corresponding to maximum pull-out forces gradually improved by peg width and strain distribution along geogrid in the PG system progressively became linear in contrast to the non-linear distribution in the conventional soil-geogrid (NG) system. Normal pressure was more influential on enhancing pull-out resistance in coarser soil. Highlights: The method suggested is novel, easy to implement, fast and does not require any equipment or skilled workers. In addition, in this reinforcement system, there is no need for screws, welds or clamps to connect the peg to the geogrid. The results of the investigation up to this stage are promising and show enhancement in pullout resistance.